Layered oxide positive electrode material of sodium ion battery and preparation method of layered oxide positive electrode material
Through the wet mixing process and the two-step sintering process, the problem of poor mixing uniformity in the preparation of sodium-ion battery cathode materials is solved, the electrochemical performance and structural stability of the material are significantly improved, and it is suitable for the application of large-scale energy storage systems.
Patent Information
- Application Number
- CN202411236296.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-04
- Publication Date
- 2025-01-21
AI Technical Summary
The existing preparation methods for layered transition metal oxide positive electrode materials of sodium ion battery have problems such as poor mixing uniformity, low performance consistency, cycle stability and rate performance degradation, and dry mixing process may lead to environmental pollution and health risks.
Using a wet mixing process, the layered oxide cathode material precursor and sodium source are prepared into slurries respectively. Through temperature control and filtration treatment, the precursor and sodium source are uniformly mixed, and then a two-step sintering process is performed to improve the material quality. electrochemical properties.
The component distribution uniformity, structural stability and electrochemical performance of the cathode material are significantly improved, including higher capacity, better cycle stability and rate performance, and are suitable for large-scale production and practical applications.
Smart Images

Figure BDA0005027814030000101
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of sodium ion batteries, and in particular relates to a sodium ion battery layered oxide positive electrode material and a preparation method thereof. Background Art
[0002] As the global energy crisis and environmental problems become increasingly severe, the development and utilization of renewable energy has become a hot topic in current research. The rapid development of new energy sources such as wind energy, solar energy, and geothermal energy has made large-scale, high-efficiency energy storage systems a key demand in the energy field. Among the many energy storage technologies, secondary batteries based on electrochemical principles are considered to be the most promising energy storage solution due to their high energy conversion efficiency, ease of use, and simple maintenance.
[0003] As the current mainstream secondary battery technology, lithium-ion batteries have been widely used in portable electronic devices and electric vehicles. However, the scarcity and high cost of lithium resources limit their application in large-scale energy storage systems. In contrast, sodium is abundant on Earth, widely distributed, and inexpensive, making sodium-ion batteries show great potential in large-scale application scenarios such as grid energy storage.
[0004] In recent years, research on sodium-ion battery materials has made significant progress, especially in the development of positive electrode materials. The main research directions include layered transition metal oxides, polyanionic compounds and Prussian blue compounds. Among them, layered transition metal oxides are considered to be one of the most promising electrode materials due to their advantages such as high capacity, simple synthesis process and environmental friendliness.
[0005] However, there are still many problems in the existing preparation methods of layered transition metal oxide cathode materials for sodium ion batteries. The traditional dry mixing process, that is, directly mixing the sodium source powder with the precursor powder through a mechanical mixing device and then sintering, has obvious defects such as low mixing efficiency and uneven mixing. These problems not only affect the performance consistency of the material, but may also lead to a decrease in the cycle stability and rate performance of the battery.
[0006] In addition, the dust generated during the dry mixing process may cause environmental pollution and health risks. At the same time, due to uneven mixing, local over-burning or under-sintering areas may be formed during the subsequent sintering process, further affecting the electrochemical properties and structural stability of the material.
[0007] Considering the important position of sodium-ion batteries in future large-scale energy storage systems, it is particularly urgent to develop a new and efficient method for preparing layered transition metal oxide cathode materials for sodium-ion batteries. This method should be able to solve the mixing uniformity problem in the existing technology, improve the consistency and electrochemical performance of the materials, and have good scalability and environmental friendliness to meet the needs of future large-scale production.
[0008] Therefore, the present invention aims to provide a new method for preparing a layered transition metal oxide positive electrode material for a sodium ion battery, so as to overcome the deficiencies in the prior art and promote the advancement and practical application of sodium ion battery technology. Summary of the invention
[0009] The purpose of the present invention is to provide a method for preparing a layered oxide positive electrode material for a sodium ion battery, which effectively solves the problem of poor mixing uniformity of the existing sodium source and the layered oxide precursor, thereby improving the consistency and electrochemical performance of the layered oxide positive electrode material.
[0010] In order to achieve the above object, the present invention adopts the following technical solutions:
[0011] A method for preparing a sodium ion battery layered oxide positive electrode material comprises the following steps:
[0012] 1) Mixing a layered oxide cathode material precursor with a 50-60° C. solvent to prepare a precursor slurry, wherein the mass ratio of the precursor to the solvent is 1:1.2-1.4, and the temperature is controlled at 40-80° C. during the mixing process;
[0013] 2) mixing a sodium source with a 50-60° C. solvent to prepare a sodium-containing slurry, wherein the mass ratio of the sodium source to the solvent is 1:1.3-1.4, and the temperature is controlled at 40-80° C. during the mixing process;
[0014] 3) mixing the precursor slurry and the sodium-containing slurry to obtain a mixed slurry, and controlling the temperature at 40 to 80° C. during the mixing process;
[0015] 4) filtering the mixed slurry to obtain a filter paste;
[0016] 5) drying the filter paste, and controlling the mass content of the solvent in the filter paste to be ≤2%;
[0017] 6) The dried filter paste is subjected to a primary sintering, and the primary sintered material is crushed and sieved and then subjected to a secondary sintering to obtain a sodium ion battery layered oxide positive electrode material.
[0018] Preferably, in step 4), the mixed slurry is filtered under reduced pressure, and the mass content of the solvent in the filter paste is controlled to be 10% to 20%.
[0019] Preferably, the chemical formula of the layered oxide positive electrode material precursor is Ni x Mn y M z (OH) 2 , wherein M is at least one of Cu, Fe, Ti, V, Cr, and Co, wherein 0.1≤x≤0.6, 0.1≤y≤0.5, and 0.1≤z≤0.5;
[0020] The chemical general formula of the layered oxide cathode material is Na a NO 2 , where 0 < a ≤ 1, N is a transition metal element, and N is at least one of Ti, V, Cr, Mn, Fe, Co, Ni, and Cu.
[0021] Preferably, in step 6), the primary sintering temperature is 700 - 1000 °C, the primary sintering time is 5 - 30 h, the heating and cooling rate of the primary sintering is 1 - 15 °C / min, the primary sintering atmosphere is air, and the ventilation flow rate is 1 - 30 L / min.
[0022] Preferably, in step 6), the secondary sintering temperature is 300 - 950 °C, the secondary sintering holding time is 5 - 20 h, the heating and cooling rate of the secondary sintering is 1 - 15 °C / min, the secondary sintering atmosphere is air, and the ventilation flow rate is 1 - 20 L / min.
[0023] Preferably, the sodium source is at least one of sodium carbonate and sodium hydroxide; the solvent is at least one of methanol, absolute ethanol, and acetone.
[0024] Preferably, in step 1), a pore-forming agent is added to the precursor slurry to form a porous structure of the precursor slurry, so as to fully disperse the sodium source; the pore-forming agent is sodium bicarbonate or ammonium bicarbonate, and the mass ratio of the pore-forming agent to the precursor is 0.01 - 0.05:1.
[0025] Preferably, in step 3), a foaming agent is added to the mixed slurry, and the foaming agent volatilizes to form an air flow, so as to fully mix and disperse the precursor slurry and the sodium source slurry; the foaming agent is sodium bicarbonate or ammonium bicarbonate, and the mass ratio of the foaming agent to the mixed slurry is 0.005 - 0.02:1.
[0026] Preferably, in step 3), an inert gas bubbler is introduced during the mixing of the slurry for dispersion, the inert gas is nitrogen or argon, the gas flow rate is 0.1 - 0.5 L / min, and the dispersion time is 10 - 30 min.
[0027] In addition, the present invention also provides a layered oxide cathode material for a sodium-ion battery, which is prepared by the preparation method of the layered oxide cathode material for a sodium-ion battery described in any of the above paragraphs. The layered oxide cathode material for a sodium-ion battery prepared by the present invention has a more uniform component distribution, a more stable structure, and more excellent electrochemical performance; compared with the layered oxide cathode material prepared by the existing dry mixing method, it has a higher capacity, better cycle stability, and better rate performance, and is more conducive to the practical application of sodium-ion batteries.
[0028] Compared with the prior art, the present invention has at least the following beneficial effects:
[0029] 1) The present invention adopts a wet method to mix the precursor and the sodium source, which can significantly improve the mixing uniformity of the precursor and the sodium source compared to the dry mixing in the prior art. By preparing the precursor and the sodium source into slurries respectively and then mixing them, the two can achieve full contact and uniform distribution on a microscopic scale, avoiding the local sodium-rich or sodium-deficient phenomenon that is prone to occur in dry mixing.
[0030] 2) The present invention optimizes the temperature control of the mixing process and controls the mixing temperature at 40-80°C. On the one hand, it can reduce the viscosity of the solvent and improve the mixing efficiency; on the other hand, it can avoid the rapid volatilization of the solvent due to excessively high temperature and ensure the uniformity of the system; at the same time, the preparation temperature of the raw material slurry is close to the mixing temperature, which can minimize the adverse effects of the temperature gradient.
[0031] 3) The present invention adopts a two-step sintering process, wherein the primary sintering temperature is relatively high, which can promote the full reaction between the sodium source and the precursor; and the secondary sintering temperature is moderate, which can prevent the volatilization and loss of sodium while ensuring the crystallinity of the product. DETAILED DESCRIPTION
[0032] In order to make the technical solutions and advantages of the present invention clearer, the technical solutions of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] According to the first aspect of the present application, the present application provides a method for preparing a layered oxide positive electrode material for a sodium ion battery, comprising the following steps:
[0034] 1) Mixing a layered oxide positive electrode material precursor with a 50-60° C. solvent to prepare a precursor slurry, wherein the mass ratio of the precursor to the solvent is 1:1.2-1.4, and the temperature during the mixing process is controlled at 40-80° C., preferably 40-60° C.;
[0035] 2) mixing a sodium source with a 50-60° C. solvent to prepare a sodium-containing slurry, wherein the mass ratio of the sodium source to the solvent is 1:1.3-1.4, and the temperature during the mixing process is controlled at 40-80° C., preferably 40-60° C.;
[0036] 3) mixing the precursor slurry and the sodium-containing slurry to obtain a mixed slurry, wherein the temperature is controlled at 40 to 80° C., preferably 40 to 60° C. during the mixing process;
[0037] 4) filtering the mixed slurry to obtain a filter paste;
[0038] 5) drying the filter paste, and controlling the mass content of the solvent in the filter paste to be ≤2%;
[0039] 6) Sinter the dried filter cake once, crush and screen the material after the first sintering, and then perform a second sintering to obtain the layered oxide cathode material for sodium-ion batteries.
[0040] In an embodiment according to the present application, in step 4), the filtration of the mixed slurry is carried out by vacuum filtration, and the mass content of the solvent in the filter cake is controlled to be 10% - 20%. Of course, the present application can also be filtered at normal temperature and pressure. The present application preferably uses vacuum filtration, which can effectively control the solvent content of the filter cake, obtain a well-mixed filter cake, and remove excess solvent to facilitate subsequent drying.
[0041] In an embodiment according to the present application, in step 5), the filter cake is vacuum dried at 60 - 80 °C for 12 - 36 h. For example, the drying temperature can be 60 °C, 65 °C, 70 °C, 75 °C, 80 °C, etc., and the drying time can be 12 h, 18 h, 20 h, 24 h, 28 h, 32 h, 36 h, etc.
[0042] In an embodiment according to the present application, the chemical general formula of the layered oxide cathode material precursor is Ni x Mn y M z (OH) 2 , where M is at least one of Cu, Fe, Ti, V, Cr, Co, and 0.1 ≤ x ≤ 0.6, 0.1 ≤ y ≤ 0.5, 0.1 ≤ z ≤ 0.5;
[0043] The chemical general formula of the layered oxide cathode material is Na a NO 2 , where 0 < a ≤ 1, N is a transition metal element, and N is at least one of Ti, V, Cr, Mn, Fe, Co, Ni, Cu.
[0044] In an embodiment according to the present application, in step 6), the first sintering temperature is 700 - 1000 °C, preferably 750 - 950 °C; the first sintering time is 5 - 30 h, preferably 8 - 20 h; the heating and cooling rate of the first sintering is 1 - 15 °C / min, preferably 2 - 10 °C / min; the first sintering atmosphere is air, and the ventilation flow rate is 1 - 30 L / min, preferably 1 - 20 L / min.
[0045] In one embodiment of the present application, in step 6), the secondary sintering temperature is 300-950°C, preferably 500-950°C; the secondary sintering holding time is 5-20h, preferably 5-15h; the secondary sintering heating and cooling rate is 1-15°C / min, preferably 2-10°C / min; the secondary sintering atmosphere is air, and the ventilation flow rate is 1-20L / min, preferably 1-15L / min.
[0046] Among them, the present application adopts a two-step sintering process, in which the primary sintering temperature is relatively high, which can promote the full reaction of the sodium source and the precursor; the secondary sintering temperature is moderate, which prevents the volatilization and loss of sodium while ensuring the crystallinity of the product; the optimized sintering temperature, time, atmosphere and other conditions can obtain the target product with uniform composition and stable structure.
[0047] In one embodiment of the present application, the sodium source is at least one of sodium carbonate and sodium hydroxide; the solvent is at least one of methanol, anhydrous ethanol, and acetone, which can achieve better solubility and mixing effect.
[0048] In one embodiment according to the present application, in step 6), the mesh number of the primary sintered material crushed and sieved is 150 to 250 meshes, preferably 200 meshes. Among them, by crushing and sieving the material after the primary sintering, the agglomerates or large particles that may be formed during the sintering process can be effectively eliminated to ensure the uniformity of the material. Secondly, controlling the material within a suitable particle size range is beneficial to heat conduction and material diffusion during the secondary sintering process, thereby improving the effect of the secondary sintering. In addition, the appropriate particle size can increase the specific surface area of the material, improve the reactivity of the material during the secondary sintering process, and help form a more ideal crystal structure. In addition, a suitable particle size distribution can reduce excessive shrinkage during the secondary sintering process and help maintain the structural integrity of the material.
[0049] In one embodiment according to the present application, in step 6), the material after secondary sintering is sieved, and the mesh number of the sieve is 350 to 450 meshes, preferably 400 meshes. Among them, screening the final product can more accurately control the particle size distribution of the material to ensure the uniformity and consistency of the product. Secondly, a finer and more uniform particle size distribution is conducive to the preparation of electrode slurry, which can improve the density and uniformity of the electrode, thereby improving the overall performance of the battery. In addition, the appropriate particle size can provide a larger specific surface area, which is conducive to the penetration of the electrolyte and the transmission of ions, thereby improving the electrochemical activity and rate performance of the material. In addition, a uniform particle size distribution can reduce stress concentration in the electrode, improve the structural stability of the electrode, and help to increase the cycle life of the battery.
[0050] In one embodiment of the present application, in step 1), a pore-forming agent is added to the precursor slurry to form a porous structure of the precursor slurry, thereby fully dispersing the sodium source; the pore-forming agent is sodium bicarbonate or ammonium bicarbonate, and the mass ratio of the pore-forming agent to the precursor is 0.01 to 0.05:1, for example, it can be 0.01:1, 0.02:1, 0.03:1, 0.04:1 or 0.05:1, etc. Among them, adding a pore-forming agent to the precursor slurry can form a porous structure in the precursor to increase the specific surface area; this porous structure can fully accommodate and disperse the sodium source added subsequently, further improve the uniformity of the system, and provide more channels for the insertion and extraction of sodium ions, which is conducive to the performance of electrochemical performance.
[0051] In one embodiment of the present application, in step 3), a foaming agent is added to the mixed slurry, and the foaming agent volatilizes to form an airflow, so that the precursor slurry and the sodium source slurry are fully mixed and dispersed; the foaming agent is sodium bicarbonate or ammonium bicarbonate, and the mass ratio of the foaming agent to the mixed slurry is 0.005 to 0.02:1, for example, it can be 0.005:1, 0.01:1, 0.015:1 or 0.02:1, etc. Among them, adding a foaming agent to the mixed slurry can generate airflow during the mixing process, and the stirring effect of these airflows can break the viscosity gradient of the slurry, overcome the stratification phenomenon during the mixing process, and enable the system components to be fully mixed and evenly dispersed.
[0052] In one embodiment of the present application, in step 3), an inert gas bubbler is introduced to disperse the mixed slurry, the inert gas is nitrogen or argon, the gas flow rate is 0.1-0.5L / min, and the dispersion time is 10-30min, preferably 20-30min, wherein the dispersion time can be set according to actual conditions, and is as consistent as possible with the stirring time of the mixed slurry. Among them, the introduction of inert gas bubbling can generate a large number of tiny bubbles during the mixing process, and the stirring action of these bubbles can break the viscosity gradient of the slurry, overcome the stratification phenomenon during the mixing process, and enable the system components to be fully mixed and evenly dispersed. In addition, the use of nitrogen or argon for dispersion can not only promote mixing, but also prevent material oxidation and protect material properties.
[0053] According to the second aspect of the present application, the present application also provides a sodium ion battery layered oxide positive electrode material, which is prepared by the preparation method of the sodium ion battery layered oxide positive electrode material described in any of the above paragraphs.
[0054] The sodium ion battery layered oxide positive electrode material prepared by the present invention has a more uniform component distribution, a more stable structure, and better electrochemical performance; compared with the layered oxide positive electrode material prepared by the existing dry mixing method, it has a higher capacity, better cycle stability, and better rate performance, and is more conducive to the practical application of sodium ion batteries.
[0055] The implementation and advantages of the present invention are further described below through specific embodiments.
[0056] Example 1
[0057] A method for preparing a sodium ion battery layered oxide positive electrode material comprises the following steps:
[0058] 1) Ni 0.33 Fe 0.33 Mn 0.33 (OH) 2 Mixing with 50°C anhydrous ethanol solvent to prepare a precursor slurry, the mass ratio of the precursor to anhydrous ethanol is 1:1.3, and the temperature is controlled at 50°C during the mixing process;
[0059] 2) mixing sodium carbonate with anhydrous ethanol solvent at 50° C. to prepare a sodium-containing slurry, wherein the mass ratio of sodium carbonate to anhydrous ethanol is 1:1.4, and the temperature is controlled at 50° C. during the mixing process;
[0060] 3) slowly adding the sodium-containing slurry prepared in step 2) into the precursor slurry prepared in step 1), stirring for 30 minutes to obtain a mixed slurry, wherein the temperature is controlled at 50° C. during the mixing process;
[0061] 4) filtering the mixed slurry obtained in step 3) under reduced pressure to control the ethanol content of the filter paste to be 15%;
[0062] 5) drying the filter paste obtained in step 4) under vacuum at 60° C. for 24 h, so that the ethanol content of the filter paste is ≤ 2%;
[0063] 6) The dried filter paste in step 5) is placed in an atmosphere furnace for primary sintering, sintered at 950°C in an air atmosphere for 15 hours, the heating rate is 5°C / min, and the ventilation flow rate is 20L / min, to obtain a primary sintered material; the primary sintered material is crushed through a 200-mesh sieve, and then placed in an atmosphere furnace for secondary sintering, sintered at 900°C in an air atmosphere for 10 hours, the heating rate is 5°C / min, and the ventilation flow rate is 15L / min; after sintering, the layered oxide positive electrode material for sodium ion batteries is obtained, and its chemical formula is NaNi 0.33 Fe 0.33 Mn 0.33 O 2 .
[0064] Example 2
[0065] The difference from Example 1 is that in step 1), a sodium bicarbonate pore-forming agent is added to the precursor slurry, and the mass ratio of sodium bicarbonate to the precursor is 0.03: 1. The addition of the pore-forming agent can form a porous structure in the precursor slurry, thereby fully dispersing the sodium source in the subsequent mixing process, further improving the uniformity of the product.
[0066] The rest is the same as in Example 1 and will not be described again here.
[0067] Example 3
[0068] The difference from Example 1 is that in step 3), an ammonium bicarbonate foaming agent is added to the mixed slurry, and the mass ratio of ammonium bicarbonate to the mixed slurry is 0.01: 1. The foaming agent decomposes and generates bubbles during the mixing process, which has a stirring and dispersing effect on the slurry, and can effectively promote the uniform mixing of the precursor slurry and the sodium source slurry.
[0069] The rest is the same as in Example 1 and will not be described again here.
[0070] Example 4
[0071] The difference from Example 1 is that in step 3), nitrogen is introduced to disperse bubbles when mixing the slurry, the nitrogen flow rate is 0.3 L / min, and the dispersion time is 30 min. Inert gas bubbling can form tiny bubbles inside the slurry, destroy the surface tension of the slurry, and play an effect similar to surfactant emulsification, making the slurry mixing more uniform.
[0072] The rest is the same as in Example 1 and will not be described again here.
[0073] Example 5
[0074] The difference from Example 1 is that: in step 1), sodium bicarbonate pore-forming agent is added to the precursor slurry, and the mass ratio of sodium bicarbonate to precursor is 0.03:1; in step 3), ammonium bicarbonate foaming agent is added to the mixed slurry, and the mass ratio of ammonium bicarbonate to the mixed slurry is 0.01:1; in step 3), nitrogen is introduced into the mixed slurry for bubble dispersion, the nitrogen flow rate is 0.3L / min, and the dispersion time is 20min.
[0075] The rest is the same as in Example 1 and will not be described again here.
[0076] Comparative Example 1
[0077] The difference from Example 1 is that the layered oxide positive electrode material for sodium ion battery is prepared by dry mixing using the existing technology, that is, Ni 0.33 Fe 0.33 Mn 0.33 (OH) 2 The precursor was dry-mixed with sodium carbonate powder in a stoichiometric ratio and sintered under the same conditions to obtain NaNi 0.33 Fe 0.33 Mn 0.33 O 2 Positive electrode material.
[0078] The positive electrode materials prepared in the above examples and comparative examples were assembled into a CR2032 type sodium ion half-cell, with a metal sodium sheet as the negative electrode and 1 mol / L NaPF 6 EC:DEC (volume ratio 1:1) solution was used as the electrolyte to test the electrochemical performance. The test results are shown in Table 1 below.
[0079] 1. Test of the first week discharge capacity (mAh / g):
[0080] 1) After the assembled battery is left at room temperature for 12 hours, a constant current charge and discharge test is performed at a current density of 0.1C (1C = 120mA / g) in the voltage range of 2.0 to 4.0V for the first week;
[0081] 2) The first-week discharge specific capacity (mAh / g) of the positive electrode material is obtained by dividing the first-week discharge capacity (mAh) by the mass (g) of the positive electrode material.
[0082] 2. Test of discharge specific capacity (mAh / g) after 100 cycles:
[0083] 1) After completing the first week discharge capacity test, a constant current charge and discharge cycle test was performed continuously for 100 times at a current density of 0.5C (1C = 120mA / g) in the voltage range of 2.0 to 4.0V.
[0084] 2) The discharge capacity (mAh) of the 100th cycle was divided by the mass (g) of the positive electrode material to obtain the discharge specific capacity (mAh / g) of the positive electrode material after 100 cycles.
[0085] 3. Test of 1C rate discharge capacity (mAh / g):
[0086] 1) After completing 100 cycle tests, the battery was subjected to a constant current charge and discharge test at a current density of 1C (1C = 120 mA / g) in a voltage range of 2.0 to 4.0 V;
[0087] 2) The discharge capacity (mAh) at 1C rate was divided by the mass (g) of the positive electrode material to obtain the discharge specific capacity (mAh / g) of the positive electrode material at 1C rate.
[0088] Table 1
[0089]
[0090] The test results in Table 1 are analyzed as follows:
[0091] 1. Comparative analysis of experimental results of embodiments and comparative examples:
[0092] It can be seen from the above experimental data that the electrochemical performance of the sodium ion battery layered oxide positive electrode materials prepared in Examples 1 to 5 of the present invention are significantly better than those of the comparative examples. Specifically:
[0093] 1) In terms of the first-week discharge specific capacity, the capacity range of Examples 1 to 5 is 140.2 to 148.9 mAh / g, while the capacity of the comparative example is only 128.3 mAh / g. It can be seen that the first-week discharge specific capacity of the embodiments of the present invention is greatly improved compared with the comparative example, indicating that the positive electrode material prepared by the wet mixing process of the present invention can release a higher specific capacity.
[0094] 2) After 100 cycles, the discharge capacity of Examples 1 to 5 ranges from 123.6 to 133.6 mAh / g, while the 100-cycle capacity of the comparative example is only 96.2 mAh / g. It can be seen that the 100-cycle capacity of the embodiments of the present invention is significantly higher than that of the comparative example, and the cycle capacity retention rate is also significantly higher than that of the comparative example, indicating that the cycle stability of the positive electrode material prepared by the present invention is much better than that of the comparative example.
[0095] 3) In terms of 1C rate discharge specific capacity, the capacity range of Examples 1 to 5 is 107.5 to 118.5 mAh / g; while the capacity of the comparative example at 1C rate drops sharply to 80.6 mAh / g. It can be seen that the 1C rate capacity of the embodiments of the present invention is greatly improved compared with the comparative example, indicating that the positive electrode material prepared by the present invention exhibits excellent rate performance at high rate charge and discharge, while the rate performance of the comparative example is seriously insufficient.
[0096] In summary, the present invention adopts wet mixing of precursor slurry and sodium source slurry to prepare sodium ion battery positive electrode material, and the comprehensive electrochemical properties of the obtained product, such as specific capacity, cycle stability, and rate performance, are significantly better than those of the positive electrode material prepared by dry mixing in the prior art. It shows that the present invention adopts a wet mixing process to prepare sodium ion battery layered oxide positive electrode material, and by preparing the precursor and the sodium source into slurry respectively and then mixing them, the two can achieve full contact and uniform distribution on a microscopic scale, combined with optimized temperature control and a two-step sintering process, and finally obtains a sodium ion battery positive electrode material with uniform components, stable structure, and excellent electrochemical performance, which shows outstanding advantages such as high capacity, high rate, and long life in practical applications.
[0097] 2. Comparative analysis of experimental results between various embodiments:
[0098] Further comparison of the experimental data of Examples 1 to 5 shows that after introducing the preferred measures such as pore formers, foaming agents, and inert gas dispersion in Examples 2 to 5, the performance of the obtained positive electrode materials is improved to varying degrees compared with that in Example 1. Among them:
[0099] 1) In Example 2, a pore former is added to the precursor slurry, and the first-week discharge specific capacity, 100-cycle capacity and 1C rate capacity of the obtained positive electrode material are respectively higher than those of Example 1. It can be seen that the addition of the pore former can form a porous structure in the precursor, and the sodium source can be more fully dispersed in the subsequent mixing process, thereby improving the specific capacity and cycle performance of the product.
[0100] 2) Example 3: A foaming agent is added to the mixed slurry, and the first-week discharge specific capacity, 100-cycle capacity and 1C rate capacity of the obtained positive electrode material are respectively higher than those of Example 1. It can be seen that the bubbles generated by the foaming agent have an effective stirring and dispersing effect on the slurry, further promoting the uniform mixing of the precursor and the sodium source, so that the specific capacity and rate performance of the product are more significantly improved.
[0101] 3) Example 4 uses inert gas bubbling to disperse the mixed slurry, and the first week discharge specific capacity, 100 cycle capacity and 1C rate capacity of the obtained positive electrode material are respectively higher than those of Example 1. It can be seen that the inert gas bubbling dispersion can form tiny bubbles inside the slurry, which destroys the surface tension of the slurry to the maximum extent, similar to the effect of surfactant emulsification, so that the slurry achieves the best mixing uniformity, so the prepared positive electrode material has excellent specific capacity, cycle stability and rate performance.
[0102] 4) In Example 5, a pore-forming agent is added to the precursor slurry, a foaming agent is added to the mixed slurry, and an inert gas is used to disperse the mixed slurry by bubbling. The first-week discharge specific capacity, 100 cycle capacity and 1C rate capacity of the obtained positive electrode material are significantly higher than those of Example 1, and various performance indicators are better than those of other examples.
[0103] In summary, compared with the basic embodiment 1, the preferred embodiments of the present invention can further enhance the mixing uniformity of the precursor and the sodium source by introducing pore formers, foaming agents, bubble dispersion and the like during the mixing process, so that the electrochemical performance of the obtained sodium ion battery layered oxide positive electrode material is comprehensively improved, among which the dispersion effect of simultaneously introducing pore formers, foaming agents and inert gas bubbling is the best.
[0104] According to the disclosure and teaching of the above description, those skilled in the art to which the present invention belongs can also change and modify the above embodiment. Therefore, the present invention is not limited to the above specific embodiment, and any obvious improvement, replacement or modification made by those skilled in the art on the basis of the present invention belongs to the protection scope of the present invention. In addition, although some specific terms are used in this specification, these terms are only for the convenience of description and do not constitute any limitation to the present invention.
Claims
1. A method for preparing a layered oxide positive electrode material for a sodium ion battery, characterized in that: The following steps are involved: 1) Mixing a layered oxide cathode material precursor with a 50-60° C. solvent to prepare a precursor slurry, wherein the mass ratio of the precursor to the solvent is 1:1.2-1.4, and the temperature is controlled at 40-80° C. during the mixing process; 2) mixing a sodium source with a 50-60° C. solvent to prepare a sodium-containing slurry, wherein the mass ratio of the sodium source to the solvent is 1:1.3-1.4, and the temperature is controlled at 40-80° C. during the mixing process; 3) mixing the precursor slurry and the sodium-containing slurry to obtain a mixed slurry, and controlling the temperature at 40 to 80° C. during the mixing process; 4) filtering the mixed slurry to obtain a filter paste; 5) drying the filter paste, and controlling the mass content of the solvent in the filter paste to be ≤2%; 6) The dried filter paste is subjected to a primary sintering, and the primary sintered material is crushed and sieved and then subjected to a secondary sintering to obtain a sodium ion battery layered oxide positive electrode material.
2. The method for preparing the layered oxide positive electrode material for sodium ion batteries according to claim 1, characterized in that: In step 4), the mixed slurry is filtered under reduced pressure, and the mass content of the solvent in the filter paste is controlled to be 10% to 20%.
3. The method for preparing the layered oxide positive electrode material for sodium ion batteries according to claim 1, characterized in that: The chemical formula of the layered oxide positive electrode material precursor is Ni x Mn y M z (OH)2, wherein M is at least one of Cu, Fe, Ti, V, Cr, and Co, wherein 0.1≤x≤0.6, 0.1≤y≤0.5, and 0.1≤z≤0.5; The chemical general formula of the layered oxide cathode material is Na a NO2, where 0 < a ≤ 1, N is a transition metal element, and N is at least one of Ti, V, Cr, Mn, Fe, Co, Ni, and Cu.
4. The method for preparing the layered oxide positive electrode material for sodium ion batteries according to claim 1, characterized in that: In step 6), the primary sintering temperature is 700-1000° C., the primary sintering time is 5-30 h, the primary sintering heating and cooling rate is 1-15° C. / min, the primary sintering atmosphere is air, and the ventilation flow rate is 1-30 L / min.
5. The method for preparing the layered oxide positive electrode material for sodium ion batteries according to claim 1 or 4, characterized in that: In step 6), the secondary sintering temperature is 300-950°C, the secondary sintering holding time is 5-20h, the secondary sintering heating and cooling rate is 1-15°C / min, the secondary sintering atmosphere is air, and the ventilation flow rate is 1-20L / min.
6. The method for preparing the layered oxide positive electrode material for sodium ion batteries according to claim 1, characterized in that: The sodium source is at least one of sodium carbonate and sodium hydroxide; the solvent is at least one of methanol, anhydrous ethanol and acetone.
7. The method for preparing the layered oxide positive electrode material for sodium ion batteries according to claim 1, characterized in that: In step 1), a pore former is added to the precursor slurry to form a porous structure of the precursor slurry, thereby fully dispersing the sodium source; the pore former is sodium bicarbonate or ammonium bicarbonate, and the mass ratio of the pore former to the precursor is 0.01 to 0.05:
1.
8. The method for preparing the layered oxide positive electrode material for sodium ion batteries according to claim 1, characterized in that: In step 3), a foaming agent is added to the mixed slurry, and the foaming agent volatilizes to form an airflow, so that the precursor slurry and the sodium source slurry are fully mixed and dispersed; the foaming agent is sodium bicarbonate or ammonium bicarbonate, and the mass ratio of the foaming agent to the mixed slurry is 0.005 to 0.02:
1.
9. The method for preparing the layered oxide positive electrode material for sodium ion batteries according to claim 1, characterized in that: In step 3), an inert gas bubbler is introduced to disperse the mixed slurry, wherein the inert gas is nitrogen or argon, the gas flow rate is 0.1 to 0.5 L / min, and the dispersion time is 10 to 30 min.
10. A layered oxide positive electrode material for a sodium ion battery, characterized in that: The sodium ion battery layered oxide positive electrode material is prepared by the preparation method of any one of claims 1 to 9.
Citation Information
Patent Citations
Method for preparing ternary cathode material through combination of pre-sintering and impregnating and lithium battery
CN110294499A
High-nickel single-crystal nickel-cobalt-aluminum ternary positive electrode material and preparation method thereof
CN113422046A
Nickel-iron-manganese layered oxide as well as preparation method and application thereof
CN116282222A
Heat treatment method of metal oxide positive electrode material of sodium ion battery, sodium ion secondary battery and preparation method of sodium ion secondary battery
CN118084076A
Cited By
Preparation method of sodium ion battery cathode material, cathode plate and sodium ion battery
CN120015806A